Faults Identification and Corrective Actions in Rotating Machinery at Rated Speed - Nicolò Bachschmid; Paolo Pennacchi (Shock and Vibration)
Malfunction identification in rotor systems by means of a model based approach in the frequency domain during long lasting speed transients (coast-down procedures in large turbo-generators), where a huge amount of vibration data at different rotating speeds is usually collected, has proved to be very effective. This paper explores the possibility to adapt this method to the situation when the vibration data are available at one rotating speed only, which in real machines is generally the normal operating speed. It results that single speed fault identification can be successful, but does not allow to discriminate between different malfunctions that generate similar symptoms. Neverthless the identification results can be used to define corrective balancing masses.